Mechanical, Morphological and Hygroscopic Characterization of Bio-Composites Reinforced with Untreated and Alkali-Treated Grewia flavescens Fibers - Yugesh Mani Tiwari; Saroj Kumar Sarangi; Ashwani Kumar Singh; P. Senthamaraikannan; Indran Suyambulingam; R. Kumar (Journal of Natural Fibers)
As the world shifts toward biodegradable materials to reduce environmental pollution, natural fiber-reinforced composites are gaining attention as sustainable alternatives to synthetic composites. However, natural fibers exhibit high moisture absorption and poor interfacial bonding with polymer matrices, affecting the mechanical properties of the composites. This study addresses these challenges by reinforcing polyester resin with untreated and alkali-treated Novel Grewia flavescens fiber (GFF) to enhance composite performance. Alkali treatment (5% NaOH, 45 min) was used to reduce fiber hydrophilicity and improve surface roughness, leading to better fiber-matrix adhesion. Composites were fabricated using the short fiber with fiber loadings of 10%, 20%, 30%, 40%, and 50% by weight. Mechanical characterization, including tensile, flexural, and impact tests, revealed that the optimal mechanical properties were achieved at 40% fiber reinforcement, with treated fibers outperforming untreated ones. A hygroscopic test further evaluated the water absorption behavior of the composites. The findings demonstrate that alkali treatment significantly improves the mechanical and moisture resistance properties of Grewia flavescens fiber-reinforced polyester composites, making them a promising material for eco-friendly applications